2019
DOI: 10.1186/s13098-019-0414-1
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal assessment of participants in a long distance walk

Abstract: Background Exercise can disrupt homeostasis and trigger many adaptive responses in different hormonal axes. The study of hormonal interactions with physical activity is highly complex due to the number of variables, such as exercise duration, exercise intensity, individual level of training, circadian rhythm, nutritional status, and environmental conditions. Methods This study was performed to assess daily variations of thyroid hormones, cortisol, testosterone, insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
2
4
0
2
Order By: Relevance
“…22 Exercise may decrease cortisol by improving mood and increasing brain neurotransmitters, as well as acting as a distractor from negative thoughts. hs-CRP is an acute inflammatory marker associated with PMS.Therefore, it is an important outcome for patients with PMS.…”
mentioning
confidence: 99%
“…22 Exercise may decrease cortisol by improving mood and increasing brain neurotransmitters, as well as acting as a distractor from negative thoughts. hs-CRP is an acute inflammatory marker associated with PMS.Therefore, it is an important outcome for patients with PMS.…”
mentioning
confidence: 99%
“…Moreover, sensitivity analysis and subgroup analyses showed an influence of exercise type (aerobic exercise) on lowering cortisol concentrations. Also, de Souza et al (25) found a reduction trend in blood cortisol levels in response to daily moderate to high intensity aerobic exercise for 5 consecutive days. These findings highlight an adaptive hormonal mechanism in response to repeated stress, as shown by reduced cortisol levels.…”
Section: Discussionmentioning
confidence: 95%
“…In addition it was shown that long term exercise may have different impacts on TSH levels than an acute exercise program (Hawamdeh, Baniata, Mansi, Nasr, Aburjai, 2012). However, no changes in circulating TSH were observed in elite athletes who underwent regular training (Healy, Gibney, Pentecost, Wheeler, Sonksen, 2014;de Souza et al, 2019;Ceresini et al, 2019). With this background in mind our study was undertaken and was aimed at evaluation of relationships between circulating TSH within the normal range with metabolic risk factors (glucose, insulin, lipoproteins) separately in male and female physical education students engaged in regular physical activity due to their studies.…”
Section: Introductionmentioning
confidence: 99%